The Perceptions, Willingness, and Barriers towards Participation in Telerehabilitation among Malaysian COVID-19 Patients - Hai, Su Jia; Ong, Jun Hui; Heaw, Yu Chi (INTI International University, 2023)
Background: Demand for rehabilitation in Malaysia has increased following the spike in Coronavirus disease 19 (COVID-19) cases since 2020. With limited delivery of physical therapy services, travel restrictions, and risk of virus transmissions, telerehabilitation presents an alternative to traditional rehabilitation. Previous studies have investigated the perception of telerehabilitation among healthcare professionals in Malaysia, but lack investigations on the perceptions, willingness, and barriers toward participation in telerehabilitation among Malaysian COVID-19 patients. Therefore, it is important to understand the perceptions, willingness, and barriers toward participation in telerehabilitation among Malaysian COVID-19 patients to determine the applicability of telerehabilitation in Malaysia. The purpose of this study was to identify the perceptions, willingness, and barriers toward participation in telerehabilitation among Malaysian COVID-19 patients. Methodology: This is a quantitative, cross-sectional study. The recruited Malaysian COVID-19 patients were required to fill in a self-administered online questionnaire. The data collected were analyzed using the Statistical Package for Social Science (SPSS) version 21 and presented in frequencies and percentages. Results: 166 Malaysian COVID- 19 patients were included in this study. Most participants were students aged 18-25 years old (68.1%). The participants were highly educated, had high access to technology, and had a high ability in using technological devices and the internet. Most of the participants showed good perceptions toward telerehabilitation and a high willingness to participate in telerehabilitation during (75.3%, n=125) and after (65.7%, n=109) the pandemic. The most frequently selected human and technical barriers to telerehabilitation participation were that telerehabilitation was not as effective as face-to-face physical therapy sessions (18.7%) and lack of exercise equipment (34.8%), respectively. Conclusion: Overall, most participants had high perceptions towards telerehabilitation and were willing to participate in telerehabilitation with the acknowledgment of barriers towards telerehabilitation, indicating that the implementation and development of telerehabilitation in Malaysia are possible.